Multiple-benefits of Mediterranean grasslands: livestock and honeybee foraging values and pasture qualities - Henkin Z.; Perevolotsky A.; Landau S.; Ungar E.D.; Sternberg M.; Shapira T.; Dag A.; Kaminer A.; Mandelik Y. (Ecosystem services and socio-economic benefits of Mediterranean grasslands, 2016)
A long-term study was conducted to determine the multiple responses of pasture and livestock to different management systems in Mediterranean grassland. A grazing trial was set in the eastern Galilee, Israel, comprising two stocking densities (0.55 and 1.1 cows ha-1) and two protocols, continuous and split-paddock grazing. Growth dynamics, botanical composition, diversity and nutritional quality of the pasture were determined. Livestock production, foraging potential of honeybees and landscape visual qualities were defined as well. It was shown that intensive use of Mediterranean grassland with high stocking density during the growing season can be economically feasible. Species diversity was found to be remarkably stable across all grazing treatments. Lower relative growth rates under grazing were detected as heavier stocking density reduced standing biomass, but herbage quality increased along with grazing intensity. Cattle grazing did not decrease the forage potential of open landscapes for honeybees; some of the examined parameters even revealed positive effects. In addition to animal production, Mediterranean grasslands have significant landscape values that are becoming increasingly important, they provide a wide range of ecological services. The multiple benefits of these landscapes can justify the expense of necessary interventions that cannot be justified by any single benefit.
15. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM International Network for the Research and Development of Pastures and Fodder Crops, 2016/04/12-14, Orestiada (Greece)